A laser-optical sensor system for blade vibration detection of high-speed compressors. (December 2015) - Neumann, Mathias; Dreier, Florian; Günther, Philipp; Wilke, Ulrich; Fischer, Andreas; Büttner, Lars; Holzinger, Felix; Schiffer, Heinz-Peter; Czarske, Jürgen
Abstract: Improved efficiency as well as increased lifetime of turbines and compressors are important goals in turbomachinery development. A significant enhancement to accomplish these aims can be seen in online monitoring of the operating parameters of the machines. During the operation of compressors it is of high interest to predict critical events like flutter or stall which can be achieved by observing blade deformations and vibrations. We have developed a laser Doppler distance sensor (LDDS), which is capable of simultaneously measuring the radial blade expansions, the circumferential blade deflections as well as the circumferential velocities of the rotor blade tips. As a result, an increase of blade vibrations is measured before stall at characteristic frequencies. While the detected vibration frequencies and the vibration increase are in agreement with the measurement results of a commercial capacitive blade tip timing system, the measured values of the vibration amplitudes differ by a factor of three. This difference can be mainly attributed to the different measurement locations and to the different measurement approaches. Since the LDDS is applicable to metal as well as ceramic, carbon-fiber and glass-fiber reinforced composite blades, a universally applicable sensor system for stall prediction and status monitoring is presented. Abstract : Highlights: Blade deformations and vibrations of a compressor are measured at near stall. We found that stall can be predicted by an increase of characteristic vibrations. Vibrations are resolved with a single-probe optical sensor and signal processing. The obtained results agree with results of state-of-the-art measurement systems. The novel system is applicable at metal, ceramic and composite blades.